Like-attracts-like optimizer-based video robotics clustering control design for power device monitoring and inspection - Huang, Xuyong; Tang, Biao; Zhu, Mengmeng; Ma, Yutang; Ma, Xianlong; Tang, Lijun; Wang, Xin; Zhu, Dongdong (Frontiers in Energy Research, 2023)
This paper proposes a novel meta-heuristic algorithm called like-attracts-like optimizer (LALO). It is inspired by that an excellent person (i.e., a high-quality solution) easily attracts the like-minded persons to approach him or her. This LALO algorithm is an important inspiration for video robotics cluster control. Firstly, the searching individuals are dynamically divided into multiple clusters by a growing neural gas network according to their positions, in which the topological relations between different clusters can also be determined. Secondly, each individual will approach a better individual from its superordinate cluster and the adjacent clusters. The performance of LALO is evaluated on unimodal benchmark functions compared with various well-known meta-heuristic algorithms, which reveals that it is competitive for some optimizations.